Future scenario of China's downstream oil reform: Improving the energy-environmental efficiency of the pipeline networks through interconnectivity - Yuan, Meng; Zhang, Haoran; Wang, Bohong; Zhang, Yang; Zhou, Xingyuan; Liang, Yongtu (Energy Policy, 2020)
Improving energy supply efficiency and quality is regarded as a key pathway to shifting towards a fully sustainable energy system. To address the low efficiency and high emissions in the downstream oil industry caused by the problem of vertically integrated monopoly, the Chinese government is making an effort to promote a multiproduct pipeline network reform. The fundamental and indispensable step for this goal is the pipeline network interconnectivity. This paper quantifies the energy-environmental impacts of the pipeline network interconnectivity reform on China's downstream oil supply chain to 2030. An integrated framework is developed to obtain the detailed design-scale information required for assessment, introducing demand forecasting and demand reallocation into a pipeline network optimal planning model. The model is formulated as a fuzzy mixed integer linear programming that optimizes the infrastructure development scheme and supply chain operation plan simultaneously while taking into account demand uncertainty. The results show that, compared with the baseline, the pipeline interconnectivity reform could reduce yearly energy consumption and CO2 emissions by 9.7–19.8% and 12.5–17.9%, respectively. It is shown that this reform policy could overcome infrastructure constraints, increase pipeline utilization, and improve both energy and environmental performance. The proposed framework can be a theoretical guideline for policymakers within and beyond China. •We quantify the benefits of pipeline network interconnectivity reform in China's DOSC.•We propose an integrated framework to evaluate the energy-environmental efficiency.•Energy saving and CO2 reduction will respectively reach 9.7% and 12.5% at least.•The reform breaks the infrastructure bottleneck and improves oil supply efficiency.•Detailed policy implications are recommended for policy makers in China.